Using decision analysis to optimise R&D investment: the case of SmithKline Beecham - Clemen, Robert (Henry Stewart Talks, 2019)
This case study examines SmithKline Beecham’s use of decision analysis to determine which R&D projects to fund. This process significantly improved on the ‘project champion’ approach, resulting in a substantial increase in value for the same amount of capital investment.